Potentiation of apoptosis in drug-resistant mantle cell lymphoma cells by MCL-1 inhibitor involves downregulation of inhibitor of apoptosis proteins - Yijing Li; Heng-Huan Lee; Vivian Changying Jiang; Yuxuan Che; Joseph McIntosh; Alexa Jordan; Jovanny Vargas; Tianci Zhang; Fangfang Yan; Margaret Elizabeth Simmons; Wei Wang; Lei Nie; et al. (Cell Death and Disease, 2023)
Abstract Bruton’s tyrosine kinase inhibitors (BTKi) and CAR T-cell therapy have demonstrated tremendous clinical benefits in mantle cell lymphoma (MCL) patients, but intrinsic or acquired resistance inevitably develops. In this study, we assessed the efficacy of the highly potent and selective MCL-1 inhibitor AZD5991 in various therapy-resistant MCL cell models. AZD5991 markedly induced apoptosis in these cells. In addition to liberating BAK from the antiapoptotic MCL-1/BAK complex for the subsequent apoptosis cascade, AZD5991 downregulated inhibitor of apoptosis proteins (IAPs) through a BAK-dependent mechanism to amplify the apoptotic signal. The combination of AZD5991 with venetoclax enhanced apoptosis and reduced mitochondrial oxygen consumption capacity in MCL cell lines irrespective of their BTKi or venetoclax sensitivity. This combination also dramatically inhibited tumor growth and prolonged mouse survival in two aggressive MCL patient-derived xenograft models. Mechanistically, the augmented cell lethality was accompanied by the synergistic suppression of IAPs. Supporting this notion, the IAP antagonist BV6 induced dramatic apoptosis in resistant MCL cells and sensitized the resistant MCL cells to venetoclax. Our study uncovered another unique route for MCL-1 inhibitor to trigger apoptosis, implying that the pro-apoptotic combination of IAP antagonists and apoptosis inducers could be further exploited for MCL patients with multiple therapeutic resistance.